2010
DOI: 10.1007/s10802-010-9467-1
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Pubertal Timing and Peer Popularity for Boys and Girls: An Integration of Biological and Interpersonal Perspectives on Adolescent Depression

Abstract: The transition to adolescence marks a time of sharply increased vulnerability to the development of depression, particularly among girls. Past research has examined isolated risk factors from individual theoretical models (e.g., biological, interpersonal, and cognitive) of depression, but few have examined integrative models. This study investigated the conjoint effects of early pubertal timing and popularity in the longitudinal prediction of depressive symptoms. A total of 319 girls and 294 boys (ages 11–14) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 62 publications
3
20
1
Order By: Relevance
“…While the use of a single measurement of pubertal development is consistent with much of the research on puberty and psychopathology (e.g., Rudolph & Troop-Gordon, 2010; Stroud & Davila, 2008; Teunissen et al ., 2011), puberty is a highly dynamic process and the degree of synchrony among different markers of development may shift over time due to variations in timing and tempo (Susman et al , 2010). The present study provides a snapshot of the psychological effects of synchrony at one point in development, but may fail to capture the broader effects of synchronous versus asynchronous maturation across the pubertal transition.…”
Section: Discussionmentioning
confidence: 58%
“…While the use of a single measurement of pubertal development is consistent with much of the research on puberty and psychopathology (e.g., Rudolph & Troop-Gordon, 2010; Stroud & Davila, 2008; Teunissen et al ., 2011), puberty is a highly dynamic process and the degree of synchrony among different markers of development may shift over time due to variations in timing and tempo (Susman et al , 2010). The present study provides a snapshot of the psychological effects of synchrony at one point in development, but may fail to capture the broader effects of synchronous versus asynchronous maturation across the pubertal transition.…”
Section: Discussionmentioning
confidence: 58%
“…Some of the contexts that have been examined previously are family, neighbourhood, school and urban vs. rural area (Caspi, 1995;Dick et al, 2000;Ge et al, 1996Ge et al, , 2002Obeidallah et al, 2004). Another recent study had a similar approach in examining the link between early puberty and depressive symptoms and found that the social context, namely peer popularity, moderated the link (e.g., Teunissen et al, 2011). These prior studies have converged to show that context affects the implications of early maturation in female development.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research on associations between early pubertal timing and peer relations among girls have either used menarche (first menstruation) or combined multiple indicators of development (e.g., menarche, development of breasts, and changes in height) into a single index of pubertal development (e.g., Hamlat et al, 2015; Nadeem, 2005; Reynolds & Juvonen, 2011; Teunissen et al, 2011). Distinct from these measures of pubertal timing is a girl’s perceptions of her pubertal timing relative to her peer group.…”
Section: Perceptions Of Pubertal Timingmentioning
confidence: 99%
“…Association with peers is a commonly assumed mediating mechanism across several studies of pubertal timing effects. Early pubertal timing among girls is associated with disapproval among peers, evidenced by increasing peer victimization or negative social reputations among peers (e.g., Hamlat et al, 2015; Nadeem, 2005; Reynolds & Juvonen, 2011; Teunissen et al, 2011) and deviant peer affiliation (e.g., Ge, Brody, Conger, Simons, & Murry, 2002; Mrug et al, 2014; Negriff, Brensilver, & Trickett, 2015). These findings highlight the role of the social context in the development of early developing girls’ problem behaviors.…”
mentioning
confidence: 99%